Proceedings of the Workshop on Stylistic Variation 2017
DOI: 10.18653/v1/w17-4913
|View full text |Cite
|
Sign up to set email alerts
|

Approximating Style by N-gram-based Annotation

Abstract: The concept of style is much debated in theoretical as well as empirical terms. From an empirical perspective, the key question is how to operationalize style and thus make it accessible for annotation and quantification. In authorship attribution, many different approaches have successfully resolved this issue at the cost of linguistic interpretability: The resulting algorithms may be able to distinguish one language variety from the other, but do not give us much information on their distinctive linguistic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Our codebook was developed based on the literature 47–49 and updated during the annotation process through regular discussions among the study team ( Supplementary Appendix SA ). To capture the ambiguities present in natural communication, annotators labeled turns on a 0–3 scale, 50 with 3 implying certain relevance to symptoms. Study team consensus determined that an average score of 2 or higher indicated symptom content (the “broad gold standard”).…”
Section: Methodsmentioning
confidence: 99%
“…Our codebook was developed based on the literature 47–49 and updated during the annotation process through regular discussions among the study team ( Supplementary Appendix SA ). To capture the ambiguities present in natural communication, annotators labeled turns on a 0–3 scale, 50 with 3 implying certain relevance to symptoms. Study team consensus determined that an average score of 2 or higher indicated symptom content (the “broad gold standard”).…”
Section: Methodsmentioning
confidence: 99%
“…As we provide the annotations of two annotators for most plays, the data can also be used to investigate annotation disagreement. One may investigate if annotation disagreements point to ambiguous and potentially crucial text passages or look into the causes of disagreements (Andresen, Vauth, & Zinsmeister, 2020;Gius & Jacke, 2017).…”
Section: Reuse Potentialmentioning
confidence: 99%
“…The purpose of including the action history is to capture additional information from human input during interactive demonstrations. An extended policy π n , which operates on the extended states π n : S t,n → a t , is useful for modeling human actions in a manner similar to n-grams text models in natural language processing (NLP) (e.g., [72], [73], [74]). Of course, the analogy with n-gram models in NLP works only if both state and action spaces are discrete.…”
Section: ) Markov Decision Process With Extended Statementioning
confidence: 99%